2008
DOI: 10.1038/nature06559
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of active multiple sclerosis lesions reveals therapeutic targets

Abstract: Understanding the neuropathology of multiple sclerosis (MS) is essential for improved therapies. Therefore, identification of targets specific to pathological types of MS may have therapeutic benefits. Here we identify, by laser-capture microdissection and proteomics, proteins unique to three major types of MS lesions: acute plaque, chronic active plaque and chronic plaque. Comparative proteomic profiles identified tissue factor and protein C inhibitor within chronic active plaque samples, suggesting dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
522
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 477 publications
(555 citation statements)
references
References 36 publications
18
522
1
1
Order By: Relevance
“…It has been shown that Bc is the most prominent protein present in plaques of MS patients [198] and the CRYAB gene is the most highly induced in plaque tissue compared to normal tissue [199]. The increased expression of Bc, along with other Hsps, is proposed to be part of the oligodendrocyte's survival response [180].…”
Section: Viral Infection) Patients With Ms Have Numerous Demyelinatementioning
confidence: 99%
“…It has been shown that Bc is the most prominent protein present in plaques of MS patients [198] and the CRYAB gene is the most highly induced in plaque tissue compared to normal tissue [199]. The increased expression of Bc, along with other Hsps, is proposed to be part of the oligodendrocyte's survival response [180].…”
Section: Viral Infection) Patients With Ms Have Numerous Demyelinatementioning
confidence: 99%
“…in addition to the traditional staining of brain sections, modern molecular techniques are being used to study the contents of the MS lesions. Despite concerns about how tissues are preserved for this purpose and the caveat that post-mortem tissues may reflect only the endgame rather the ongoing disease process, some limited initial transcriptomic and 2D-mass spectrometry proteomic profiling data have been reported [79] . A cursory examination of the data reveals an enrichment of proteins important for material transport, structural integrity and adhesion.…”
Section: Challengesmentioning
confidence: 99%
“…However, much work is yet to be done to achieve a comprehensive understanding of molecular logic underlying optimal remyelination. In this regard, genomic [77], gene expression [78] and proteomic [79] analyses of MS patients will be critical.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%